Geographical Analysis of the Kirin Technique in Naruto Shippuden: A Meteorological Study of Storm Formation by Sasuke Uchiha (Universitas Pendidikan Indonesia, 2025)
Anime serves as a powerful medium that can depict natural phenomena in a visually engaging manner. This study explores the depiction of meteorological processes in the anime Naruto Shippuden, particularly through the technique Kirin used by Sasuke Uchiha. The analysis focuses on how the anime portrays storm cloud formation, condensation, cyclonic winds, and lightning, comparing these representations with real-world atmospheric and meteorological principles. Using a descriptive qualitative method, this research draws from visual scenes and scientific literature to evaluate the accuracy of the weather-related processes depicted. The findings reveal that while the anime takes creative liberties for dramatic effect, the underlying concepts reflect a basic understanding of weather modification and storm formation. This study aims to bridge scientific literacy and popular culture by showing how fiction can inspire interest in meteorological science.